GROWTH ANALYSIS OF SWINE PRODUCTION IN MANIPUR (Indian Journal of Animal Production and Management, 2015)
The present study was carried out on pigs maintained at 4 blocks of Senapati district (Manipur) considering 5 villages from each block. Twenty households from each village were selected randomly leading to 400 households under the perview of present study. Body weight at different ages had significantly influenced by pigs maintained at different villages. Significantly higher body weights were observed in pigs maintained at different villages of Purul and Mao Maram blocks than those of Kangpokpi and Saitu Gamphazol blocks. However, differences among 10 villages of former two blocks and again among 10 villages of later two blocks were nonsignificant statistically. Weights at birth, weaning, 5th month and 8th months of age varied from 0.48 + 0.01 to 0.74 + 0.02, 4.57 + 0.08 to 5.72 + 0.08, 9.55 + 0.22 to 11.85 + 0.19 and 29.80 + 0.80 to 30.48 + 0.33 Kg, respectively in different villages under study. It was concluded that body weight at different ages can be enhanced by better feeding and managemental practices.
Keywords: Growth rate; rural area; swine